AUTHENTIC ASSESSMENT IN INDONESIAN LANGUAGE LEARNING: THEORETICAL REVIEW AND ITS IMPLICATIONS - Friyandini, Ratna (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
Authentic assessment is an evaluation approach that emphasizes the importance of assessment based on real and contextual tasks in learning, so that the results reflect students’ abilities to use language communicatively and functionally. This study is a theoretical review aimed at examining the concept of authentic assessment in Indonesian language learning and identifying its implications for the learning process. This literature review examines various sources discussing the definition, characteristics, basic principles, and advantages of authentic assessment compared to traditional forms of assessment. The results of the review show that authentic assessment has great potential to increase student engagement, motivation, and critical thinking skills. Authentic assessment also supports a competency-based learning approach by emphasizing integration between mastery of material, skill development, and character building. Practical implications identified include the need to develop relevant assessment instruments, improve teacher competence in designing and implementing authentic assessments, and school policy support so that authentic assessment becomes an integral part of the Indonesian language learning process. This study recommends further research to examine the effectiveness of authentic assessment across various educational levels and Indonesian language learning contexts.